The Impact of Ecological Civilization Theory on University Students’ Pro-environmental Behavior: An Application of Knowledge-Attitude-Practice Theoretical Model - Wang, Kuan; Zhang, Lu (Frontiers in Psychology, 2021)
Environmental knowledge is considered to be one of the most important factors affecting pro-environment behavior in the environmental education of university students. First, in this paper, the ecological civilization theory was understood as a new kind of environmental knowledge. On this basis, a new theoretical model for analyzing the relationships among environmental knowledge, environmental attitude and environmental behavior was designed in this paper based on the ecological civilization theory and Knowledge-Attitude-Practice（KAP）theoretical model. Second, from the perspective of students, a questionnaire was designed for students according to the ecological civilization theory, so as to understand the level of ecological civilization theory of students. On this basis, the empirical test of the relationship between the ecological civilization theory level, pro-environment attitude level and pro-environment behavior level was carried out. The research shows that the ecological civilization theory as environmental knowledge is as important as science-oriented environmental knowledge in environmental education. As a result, the role of environmental knowledge in environmental education should not be ignored, but should enrich environmental knowledge, the ecological civilization theory should be added to the environmental knowledge system, improve the environmental knowledge education curriculum, contributing to environmental education in China.